2007
DOI: 10.1016/j.visres.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during information processing tasks: Individual differences and cultural effects

Abstract: The eye movements of native English speakers, native Chinese speakers, and bilingual Chinese/English speakers who were either born in China (and moved to the US at an early age) or in the US were recorded during six tasks: (1) reading, (2) face processing, (3) scene perception, (4) visual search, (5) counting Chinese characters in a passage of text, and (6) visual search for Chinese characters. Across the different groups, there was a strong tendency for consistency in eye movement behavior; if fixation durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
185
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(231 citation statements)
references
References 22 publications
29
185
6
1
Order By: Relevance
“…It supports findings that fixation duration is idiosyncratic (Andrews & Coppola, 1999;Rayner, Li, Williams, Cave, & Well, 2007), but it is also likely to reflect the fact that real eye movement data contain instances of refixations on the target dots, as well as occurrences in which saccades are launched from farther away when the dots are not presented in close proximity to each other. This would create a variable time lag before the target fixation commences that is absent in the ideal data.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It supports findings that fixation duration is idiosyncratic (Andrews & Coppola, 1999;Rayner, Li, Williams, Cave, & Well, 2007), but it is also likely to reflect the fact that real eye movement data contain instances of refixations on the target dots, as well as occurrences in which saccades are launched from farther away when the dots are not presented in close proximity to each other. This would create a variable time lag before the target fixation commences that is absent in the ideal data.…”
Section: Discussionsupporting
confidence: 76%
“…If we make the task easier-by increasing the targetdistractor discriminability, for instance-fixations become shorter, and saccades longer and more direct. This is further compounded by the fact that fixation durations are highly idiosyncratic (Andrews & Coppola, 1999;Rayner et al, 2007): It is likely that duration similarity will be higher in MultiMatch when comparing the scanpaths of the same person on different images than when comparing different people on the same image. This demonstrates the importance of knowing your stimuli, and the potential search strategies that your participants will use, before making predictions on the basis of the duration and length dimensions.…”
Section: Multimatch Settingsmentioning
confidence: 99%
“…Thus, we have shown a novel influence on fixation durations. It has been reported that fixation durations are sensitive to a number of factors, like the serial position of an item (SaintAubin et al, 2007), culture (Rayner et al, 2007), stimulus luminance (Loftus, 1985), and mask onset delays (Rayner et al, 2009), but to our knowledge it has not been previously shown that the use of blocked versus interleaved design plays a role.…”
Section: Blocked and Interleaved Designmentioning
confidence: 87%
“…Typical fixations during scene viewing last an average of approximately 300 ms (Hollingworth & Henderson, 2002). Several factors have been found to influence fixation durations, including: the serial position of an item (Saint-Aubin, Tremblay, & Jalbert, 2007), culture (Rayner, Li, Williams, Cave, & Well, 2007), stimulus luminance (Loftus, 1985), and the duration of the delay with which a mask appeared after fixation (Rayner, Smith, Malcolm, & Henderson, 2009). Thus, fixation durations are not fixed but are influenced by several factors, possibly reflecting top-down influences.…”
Section: Blocked Versus Interleaved Designmentioning
confidence: 99%
“…This method measuring the effect of personalization could be the relationship of users' actual behaviour in a hypermedia environment with theories that raise the issue of individual preferences and differences (Tsianos et al, 2009). The notion that there are individual differences in eye movement behaviour in information processing has already been supported at a cultural level (Rayner et al, 2007), at the level of gender differences (Mueller et al, 2008), and even in relation to cognitive style (verbal-analytic versus spatial-holistic) (Galin and Ornstein, 1974).…”
Section: Theoretical Backgroundmentioning
confidence: 98%